Blepharoptosis in Ibadan, Nigeria (2003)
Objective: To look into the cases of blepharoptosis in our environment as well as find out the causes and effects of the ptosis. Design: Prospective clinic study and prospective cluster sampling method of school children. Setting: University College Hospital, Ibadan and 3 schools in Ibadan, Nigeria. Subject: Over a 5 year period, all patients who presented with blepharoptosis at the University College Hospital were recruited for the study. During the same period, a school survey was also done to find out the prevalence of blepharoptosis among school children. Results: Twenty five cases of blepharoptosis were found during the 5 year period. Fifty two percent of the patients were found to be less than 16 years of age while only 8% were over 50 years of age. There was a 1:1 male to female ratio with majority of them (68%) having only one eye affected. The most common cause of blepharoptosis was found to be congenital, accounting for 56% of the patients. The prevalence in the school survey was found to be 1.2% higher than the incidence of 0.5% found in the eye clinic. Conclusion: Blepharoptosis is not an uncommon ocular problem. A detailed assessment of the cause, amount of ptosis and levator functions helps to determine the most appropriate surgical technique which would give the best functional and cosmetic result